2001
DOI: 10.1063/1.1396660
|View full text |Cite
|
Sign up to set email alerts
|

Modified distributed electron cyclotron resonance ion source for the production of large diameter ion beams

Abstract: The work presented in this article concerns the conception and the study of a multiantenna electron cyclotron resonance (ECR) ion source at 2.45 GHz dedicated to the surface treatment of large area materials. In this original device, a microwave plasma is created in a 20 cm in diameter ionization chamber. The 15 cm in diameter extracted ion beam has a current density of about 1 mA/cm2. The applicator is an N-way coaxial power divider in which the N=20 antennas are individually magnetized by internal SmCo bars … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2007
2007
2015
2015

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 22 publications
0
1
0
Order By: Relevance
“…Electron-cyclotron resonance (ECR) in plasma is of considerable interest for a variety of industrial applications including the usage of high-density plasma source for plasma processing and material surface modification. [19][20][21][22] Takahashi et al [23] and Kaneko et al [24] experimentally studied the propagation and damping mechanism of the left-handed polarized wave near the electron-cyclotron resonance. They have demonstrated that the absorption of the left-handed polarized wave near the ECR point in a magnetized inhomogeneous plasma results from polarization reversal in the axial direction.…”
Section: Introductionmentioning
confidence: 99%
“…Electron-cyclotron resonance (ECR) in plasma is of considerable interest for a variety of industrial applications including the usage of high-density plasma source for plasma processing and material surface modification. [19][20][21][22] Takahashi et al [23] and Kaneko et al [24] experimentally studied the propagation and damping mechanism of the left-handed polarized wave near the electron-cyclotron resonance. They have demonstrated that the absorption of the left-handed polarized wave near the ECR point in a magnetized inhomogeneous plasma results from polarization reversal in the axial direction.…”
Section: Introductionmentioning
confidence: 99%